The Impact of Dialogue and Discussion on Building Community Peace in Salah al-Din Governorate - Youth as a Model - Mustafa Khalid Jihad al-Azzawi, (Islamic Sciences Journal, 2025)
Peace in society is one of the important topics that Islam has paid attention to due to its great importance. The Glorious Quran has focused in many verses on the topic of peace. Based on the importance of the topic, I wrote this research, which will answer many questions and will benefit all members of society. Through this research, we will provide reliable information about (the impact of dialogue and discussion in building community peace in Salah al-Din Governorate - youth as a model). Salah al-Din Governorate is one of the regions that has experienced multiple social, economic, and security challenges. In light of these challenges, the role of youth emerges as a vital element in building society and achieving stability and development. Dialogue and discussion with youth are essential means of understanding their needs and channeling their energies toward effective community contribution. The concept of security in Muslim society is one of the things that Allah created man with. It helps society to have a ruling authority that looks after their affairs and works for their well-being.